(untitled) - Areen, Judith C. ([New York N.Y.], 2006)
Part of the popular University Casebook Series, Cases and Materials on Family Law provides an overview of family law, addressing traditional family law issues with an updated family model. The book covers three important themes: the tension between private ordering and state supervision in family law; constitutional doctrines invoked to limit state regulation of family law; and ethical questions unique to the field of family law. Substantially revised and updated, the fourth edition provides enriching discussion by linking key issues to important cases.
Keywords: Domestic relations,Mối quan hệ trong gia đình; United States,Hoa Kỳ